All for one, though not one for all: team players in normal tissue radiobiology. (4th March 2022) - Boerma, Marjan; Davis, Catherine M.; Jackson, Isabel L.; Schaue, Dörthe; Williams, Jacqueline P.
Abstract: Purpose: As part of the special issue on 'Women in Science', this review offers a perspective on past and ongoing work in the field of normal (non-cancer) tissue radiation biology, highlighting the work of many of the leading contributors to this field of research. We discuss some of the hypotheses that have guided investigations, with a focus on some of the critical organs considered dose-limiting with respect to radiation therapy, and speculate on where the field needs to go in the future. Conclusions: The scope of work that makes up normal tissue radiation biology has and continues to play a pivotal role in the radiation sciences, ensuring the most effective application of radiation in imaging and therapy, as well as contributing to radiation protection efforts. However, despite the proven historical value of preclinical findings, recent decades have seen clinical practice move ahead with altered fractionation scheduling based on empirical observations, with little to no (or even negative) supporting scientific data. Given our current appreciation of the complexity of normal tissue radiation responses and their temporal variability, with tissue- and/or organ-specific mechanisms that include intra-, inter- and extracellular messaging, as well as contributions from systemic compartments, such as the immune system, the need to maintain a positive therapeutic ratio has never been more urgent. Importantly, mitigation and treatment strategies, whether for the clinic, emergency use following accidental or deliberate releases, or reducing occupational risk, will likely require multi-targeted approaches that involve both local and systemic intervention. From our personal perspective as five 'Women in Science', we would like to acknowledge and applaud the role that many female scientists have played in this field. We stand on the shoulders of those who have gone before, some of whom are fellow contributors to this special issue.